Design Research to Support Fourth Grader Learn Addition of Mixed Numbers in RME Learning - Windria, Hening; Zulkardi, Zulkardi; Hartono, Yusuf (Mimbar Sekolah Dasar, 2020)
Mixed numbers andfraction in general have been a problem for students not only in understanding the concept of itself, but also in understanding the operation of it, such as addition.Thus, supporting students in learning addition of mixed numbers is needed. the aim of this study is to develop a local instructional theory and materials related to supporting students  in learning addition mixed numbers. In order to develop the theory, this studyused design research method. The is collected by generatingthe video recording of the learning process, student’s written work, students’ result from pretest and posttest, the result of interview, and also the fields note from the observation. The participants of this study are fourth grade students in one of private elementary school in Palembang. From the study,it can be seen that students have built the reasoning in addition mixed numbers. Some of them are able to use the distribution principle and use equivalence fractions when they adding the mixed numbers, and some of them are directly used the algorithm of changing mixed number to improper fractions. However, it is insufficient to say that the fractions number line has a big role in the students’ finding.